THE EVOLUTION OF TENNIS STRING TECHNOLOGY AND ITS IMPLICATION FOR PERFORMANCE AND EDUCATION IN MODERN SPORT (University Arena, 2025)
The development of tennis stringing technology has played a crucial role in shaping the modern game, influencing performance, injury prevention, and coaching strategies. This study presents a historical and technical overview of the evolution of string materials and stringing methods from the late 19th century to the present day. Starting with natural gut strings used in early wooden rackets, theresearch traces the introduction of synthetic materials in the mid-20th century and the rise of polyesterbased strings in the 1990s. Emphasis is placed on the impact of hybrid stringing patterns and lowtension setups, which have redefined power generation and spin production in high-performance tennis. The paper also explores the pedagogical implications of string technology advancements, including how physical education programs and tennis coaches can better educate young athletes on equipment selection and injury risk management. By bridging historical context with contemporary sport science, this work contributes to a more nuanced understanding of equipment’s role in athlete development and performance optimization.
Keywords: tennis; string technology; racquet sports; sport education; performance; injury prevention; equipment evolution